THE SULPHAMETHOXAZOLE BIOAVAILABILITY OF POLYMORPH IIA IN RABBITS - Siti Nurasiyah; Tedjo Yuwono (Indonesian Journal of Pharmacy, 2001)
Sulphamethoxazole, a sulphonamide antibacteria, is usually combined with trimetoprime, namely cotrimoxazole, to obtain higher potency. Because of the solubility of sulphamethoxazole in water is minute, its dissolution rate would be slow. Consequently, dissolution rate become the limiting step in the absorption process. In order to overcome this problem, therefore, some polymorph forms of sulphamethoxazole were created. The previous study found a polymorph IIA crystal form, a new modified internal crystal structure of sulphamethoxazole. This study was a continuing investigation of the bioavailability of the polymorph IIA, in capsule dosage forms, in rabbits. It was evident that the bioavailability of polymorph IIA was twice of that polymorph I. The bioavailability parameter changes of polymorph I to polymorph IIA were: the AUC increased from 872 to 1,530 mg hr L-1, the peak time (tmax) increased from 2 hours to 0.9 hours, the blood plasma level peak (Cpmax) increased from 104 to 136 mg/ L-1. Key words: bioavailability, sulphamethoxazole polymorph